Effectiveness of sensory adaptive dental environments to reduce psychophysiology responses of dental anxiety and support positive behaviours in children and young adults with intellectual and developmental disabilities: a systematic review and meta-analyses - Kaitlyn Reynolds; Ritesh Chimoriya; Navira Chandio; Danielle Tracey; Archana Pradhan; Paul Fahey; Nicole Stormon; Amit Arora (BMC, 2023)
Abstract Background People with Intellectual and developmental disabilities (IDDs) experience oral health inequality due to myriad of risk factors and complex needs. Sensory processing difficulties, maladaptive behaviours and dental anxiety contribute to difficulties in receiving preventive and routine dental treatments. This study aimed to systematically review the evidence on the effectiveness of sensory adaptive dental environments (SADE) for children and young adults (up to the ages 24 years) with IDD to address cooperation and dental anxiety. Methods This review was reported according to The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. MEDLINE (Ovid), The Cochrane Library, Embase, Google Scholar, Web of Science and OT Seeker were searched using appropriate terms to identify Randomised Control Trails (RCTs) that matched inclusion criteria. Screening was conducted by two reviewers after de-duplication based on titles and abstracts followed by full text retrieval. Quality of the included studies was assessed using Cochrane Risk of Bias (ROB)-2 for crossover trials and data extracted by two reviewers. The details of the interventions and effectiveness were compared and discussed narratively, and comparable outcomes were included to meta-analyses using R software. Results A total of 622 articles were identified and five articles met eligibility for inclusion. Three studies used multi-sensory adaptations and one used single sensory adaptation of music. Narrative synthesis showed some evidence of SADE reducing magnitude and duration, although, questionable for reducing the number of maladaptive behaviours. Two studies demonstrated conflicting evidence of the effect of SADE on cooperation. Three studies demonstrated significant positive impact of SADE on psychophysiological outcomes. Despite an overall tendency to favour SADE, no statistically significant difference of maladaptive behaviours was found between SADE and regular dental environment (RDE) (Standardised mean change (SMC) = 0.51; 95% Confidence Interval (CI) -0.20 to 1.22; p = 0.161). SADE was superior to RDE (SMC -0.66; 95% CI -1.01 to -0.30; p =  < 0.001) in reducing psychophysiological responses of dental anxiety. Conclusion Current evidence suggests that adapting visual, tactile, and auditory aspects of the dental environment in a single or multi-sensory approach demonstrates small positive effects on psychophysiological responses and maladaptive behaviours of dental anxiety for people with IDD. Trial registration The title of this review was registered with PROSPERO (CRD42022322083).